(untitled) (Ghana Journal of Science, Technology and Development, 2024)
understood in the Ghanaian population. The symptomatology of intracranial aneurysms ranges from asymptomatic to subarachnoid haemorrhage, depending on the size of a particular aneurysm. The objective of this case study was to use gadolinium-enhanced MRA to radiologically describe features of intracranial berry aneurysm (IBA) in a clinically asymptomatic patient. We present a case report on a 58-year-old woman who experienced constant right-sided headaches for about a year, managed by herbal medication until her referral to the diagnostic imaging unit for radiological investigation. She underwent a series of brain magnetic resonance (MR) imaging investigations, involving pre- and post- gadolinium contrast MR angiography (MRA). Axial, sagittal and coronal brain MRI and MR angiography were conducted with 50 mg/ml gadolinium contrast and radiologically evaluated. A right posterior communicating artery aneurysm was found, suggesting compression of the oculomotor nerve, which is characteristic of intracranial berry aneurysm (IBA) and associated with her constant headaches. The patient could not afford the cost of an aneurysm coiling to treat her condition, so she was placed on prescription medication and recommended lifestyle changes to manage her condition. The case report shows the accuracy of MRA in definitive diagnosis of IBA, which could be used to better characterize suspected aneurysm on particularly small vessel MRI of patients presenting with constant unexplained headaches. Keywords: Aneurysm, headache, internal carotid artery, intracranial berry aneurysm, magnetic resonance angiography, time-of-flight.